Exercise and other nonpharmacological strategies to reduce blood pressure in older adults: a systematic review and meta-analysis - Herrod, Philip J.J.; Doleman, Brett; Blackwell, James E.M.; O’Boyle, Francesca; Williams, John P.; Lund, Jonathan N.; Phillips, Bethan E. (Elsevier, 2018)
The incidence of hypertension increases with advancing age and represents a significant burden of disease. Lifestyle modification represents the first-line intervention in treatment algorithms; however, the majority of evidence for this comes from studies involving young participants using interventions that may not always be feasible in the elderly. This manuscript presents a systematic review of all randomized controlled trials involving participants with a mean age of 65 or over investigating nonpharmacological strategies to reduce blood pressure (BP). Fifty-three randomized controlled trials were included. The majority of interventions described aerobic exercise training, dynamic resistance exercise training, or combined aerobic and dynamic resistance exercise training (COM), with limited studies reporting isometric exercise training or alternative lifestyle strategies. Aerobic exercise training, dynamic resistance exercise training, COM, and isometric exercise training all elicited significant reductions in both systolic and diastolic BP, with no additional benefit of COM compared with single modality exercise training. Three months of traditional exercise-based lifestyle intervention may produce a reduction in BP of approximately 5 mmHg systolic and 3 mmHg diastolic in older individuals, similar to that expected in younger individuals.